Descriptors for on-farm conservation and use of Butia odorata natural populations - Mistura, C.C.; Barbieri, R.L.; Castro, C.; Padulosi, S.; Alercia, A. (Cambridge University Press, 2016)
This paper aims to propose an international list of descriptors forButia odorata(jelly palm), using scientific documentation methods and farmers' knowledge to allow the germplasm characterization for conservation and sustainable use. It is an attempt to promote the development of new approaches to documenting crop genetic resources using a blend of these two sources of knowledge, frequently perceived as conflicting. This long-lived and useful palm is a neglected and subutilized species, and its genetic diversity and associated knowledge are under severe erosion. A list of 11 morphological descriptors is proposed based on observations, literature review and discussions with farmers who know and use the plant. These descriptors were used to characterize 303 adult jelly palms conservedin situ. Descriptive results are presented. Only five morphological characteristics were reported by farmers as important to discriminate individual plants, indicating that farmers have simpler and more rapid ways to differentiate diversity than do the scientists based on their uses. Standard list of descriptors developed byex situconservationists are widely used by breeders, but they rarely reach out to farmers and other user groups, a fact that limits the full use of germplasm collections around the world. Conversely, farmer-based descriptors, which are the expression of deep knowledge of diversity and its deployment by traditional communities, are rarely considered by breeders, mainly because they are not available. In this paper, we support the idea that a blend of these two methods – in a standard format – is highly strategic to promote an effectivein situconservation-through-use approach.